MODEL PENINGKATAN PROFESIONAL GURU: PENERAPAN LESSON STUDY PADA MATA PELAJARAN BIOLOGI DI KELAS XII SMA NEGERI 11 PALEMBANG - ., Riyanto . (SEMIRATA 2015, 2015)
This article contains model of teacher professionalism improvement on biology in State Senior High School (SMAN) 11 Palembang. Application of lesson study (LS) is the model used. The purpose of LS, are 1. LS application can be used as the right model to improve biology teacher professionalism in Palembang, 2. LS application is used to improve teacher pedagogic competence in making lesson design. Method used is descriptive method by observing in the class. The implementation was collaborated with high school biology teachers which are plan, do and see. Analysis results of LS can be used as 1. Upgrading ability of State Senior High School 11 Palembangâs biology teacher in making lesson design, 2. Enhancing PBM skill of biology teacher Senior High School number 11 Palembang, 3. Improving and motivating student learning activity in the class, 4. Increasing cooperation or collaboration among biology teacher in order to increase professionalism of biology teachers in Palembang, 5. Improving average grade of students mastery. In conclusion, LS is appropriate as the model to improve the professionalism of biology teacher in Palembang. It is suggested that to improve the professionalism of high school biology teacher in Palembang is to apply LS in school MGMP programe.Keywords: Study, Professional teacher, Biology and Palembang